Navigating Entry and Survival in the City: A Relational Comparison of Migrant Workers and University Students in the City of Durban. Issue 2 (1st April 2022) - Xulu-Gama, Nomkhosi; Lorgat, Aisha
ABSTRACT: Worker hostels and student residences are an important point of entry for many poor rural–urban migrants into the city of Durban. This paper brings together and reports on the findings of research conducted in two separate studies, one with hostels (KwaMashu and Thokoza) and the other at the student residences of Durban University of Technology. Hostels and institutions of higher education in KwaZulu-Natal are used as vantage points through which we understand some of the key connections, interconnections, disconnections and reconnections that are taking place in contemporary housing in South African cities. The concept of a bed-space is key for both migrants and students and informs the analysis undertaken in this paper. We also highlight the importance of the lived experiences of migrants (both students and workers) and all the connotations embedded therein.